18F-FDG PET/CT in Tuberculosis: Can Interim PET/CT Predict the Clinical Outcome of the Patients?. (April 2020) - Sood, Apurva; Mittal, Bhagwant Rai; Modi, Manish; Chhabra, Rajesh; Verma, Roshan; Rana, Nivedita; Parihar, Ashwin Singh; Satapathy, Swayamjeet; Kumar, Rajender
Abstract : Purpose of the Report: Tuberculosis (TB) is a major health problem. Activated macrophages in TB lesions show high metabolic activity and can be assessed using 18 F-FDG PET/CT. This retroprospective study was done to evaluate the utility of 18 F-FDG PET/CT in initial assessment and therapeutic response in patients with TB. Materials and Methods: Eighty-seven patients (male-to-female ratio, 46:41) diagnosed with pulmonary TB and extrapulmonary TB underwent whole-body 18 F-FDG PET/CT for initial assessment and a follow-up scan 3 to 4 months after initiation of antitubercular therapy (ATT). Visual and semiquantitative (SUVmax ) analyses were used for scan assessment. Treatment responses on interim scans were categorized as complete metabolic response (CMR), favorable response to therapy (FRT), stable disease (SD), and disease progression (DP). CMR, FRT, and SD cases were considered as responders and DP cases as nonresponders. Treatment response was correlated with clinical outcome (mortality) and ATT duration. Results: Baseline 18 F-FDG PET/CT scans were positive in all the patients and detected additional disease sites than suspected clinically in 72% patients. On interim PET/CT, 13 patients showed CMR, 43 showed FRT, 8 showed SD, and 23 showed DP. A longer duration of ATT was seen in nonresponders ( P ⩽ 0.001) than responders. During follow-up, 9/87 patients died, out of which 8 patients were of DP group and 1 patient belonged to SD. Nonresponders showed 35% mortality compared with 1.6% in the responder group ( P ⩽ 0.001). Conclusions: 18 F-FDG PET/CT is a valuable imaging modality for disease mapping and assessing therapeutic response. Treatment response in the interim PET/CT done at 3 to 4 months predicted the duration of ATT and clinical outcome of the patients.